2020
DOI: 10.1021/acsomega.0c04013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrolyte pH on the Electro-Osmotic Characteristics in Anthracite

Abstract: Accelerating the drainage of water in coal reservoirs can significantly improve the extraction efficiency of coalbed methane (CBM). The movement of water with different pH values in anthracite was tested and analyzed. The results showed that the electro-osmotic flow velocity increased first and then slightly decreased with the increase of time up to 120 h. The electro-osmotic flow was markedly strengthened under a strong acid (pH 2) or strong alkaline (pH 13) environment, and the direction of electro-osmosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“… 32 The peak near 1030 cm –1 is attributed to the stretching vibrations of Si–O–Si and Si–O–C. 33 The peak near 540 cm –1 corresponds to the vibrations of S–S. 33 The adsorption peaks near 2925, 2855, and 1430 cm –1 are slightly smaller for modified samples than unmodified samples, indicating that some of the methyl and methylene groups were removed and the adsorption capacity of coal was weaker.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 The peak near 1030 cm –1 is attributed to the stretching vibrations of Si–O–Si and Si–O–C. 33 The peak near 540 cm –1 corresponds to the vibrations of S–S. 33 The adsorption peaks near 2925, 2855, and 1430 cm –1 are slightly smaller for modified samples than unmodified samples, indicating that some of the methyl and methylene groups were removed and the adsorption capacity of coal was weaker.…”
Section: Resultsmentioning
confidence: 99%
“… 33 The peak near 540 cm –1 corresponds to the vibrations of S–S. 33 The adsorption peaks near 2925, 2855, and 1430 cm –1 are slightly smaller for modified samples than unmodified samples, indicating that some of the methyl and methylene groups were removed and the adsorption capacity of coal was weaker. 71 The decrease in CH 4 adsorption indicated that the gas seepage performance in coal was improved because of the coal matrix shrinkage effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical modification on coal, rock, and clay has attracted increasing interest all over the world. The electrochemical method can accelerate methane seepage by removing filling matters like calcite and pyrite. Meanwhile, the CH 4 adsorption decreased after electrochemical treatment due to the increase of carboxyl and other oxygen-containing groups, and the desorption ratio and diffusion coefficient increased after modification due to the strength of interaction of methane and anthracite weakened. , Unfortunately, the previous research studies mainly described the phenomena of the electrochemical process and the results, the molecular mechanism of electrochemical modification involved was limited. The molecular mechanism of the gas–liquid wetting characteristics of coal surfaces in successful CBM extraction cannot be overstated.…”
Section: Introductionmentioning
confidence: 99%